An Analysis of Determinant Factors Influencing Students’ Anxiety Levels During the Thesis Writing Process - Syarif, Naufal Qadri (Yayasan Cendekiawan Indonesia Timur, 2025)
Final-year students of the Primary School Teacher Education (PGSD) program at Universitas Negeri Makassar (UNM) in 2024 face various challenges during the thesis writing process, particularly concerning self-efficacy, coping strategies, and family support, all of which influence their anxiety levels. In Indonesia, the prevalence of anxiety disorders among individuals aged 15 and above increased from 6% in 2013 to 9.8% in 2018. This study aims to analyze the factors associated with anxiety levels among final-year PGSD UNM students during thesis preparation. This research employed an analytical survey design with a cross-sectional approach. The population consisted of 552 undergraduate PGSD students currently writing their theses, with a sample of 123 respondents selected through proportionate stratified random sampling. Data were collected using an online questionnaire via Google Form and analyzed using the Spearman Rank correlation test. Bivariate analysis showed significant correlations between self-efficacy (p = 0.001, ρ = -0.283), coping strategies (p = 0.012, ρ = 0.226), and family support (p = 0.015, ρ = 0.218) with students’ anxiety levels. These findings indicate that self-efficacy, coping strategies, and family support are significantly associated with the level of anxiety among PGSD students. Final-year students are encouraged to maintain strong motivation in completing their theses to obtain their degrees. It is essential to foster high self-efficacy, apply effective coping strategies, and seek family support to reduce anxiety during the thesis writing process.